Introduction and Goals for the National Children’s Study - Hirschfeld, Steven (Frontiers in Pediatrics, 2018)
The National Children’s Study (NCS) evolved in concept and planning to become an integrated systems based initiative to assess a full spectrum of health and capture the environmental factors and other influences that shape the trajectory of child development. The NCS built on prior work in health assessment, epidemiology, logistics, and methodology in order to address the broad goals of its mandate. To develop the specific methods and tools to conduct a study in multiple environments outside conventional health care delivery clinics the NCS invested in new approaches such as informatics, study operations, and the establishment of a Health Measurements Network to provide accurate, cost effective, and scientifically valid data that would be interoperable with data collected by other longitudinal studies around the world as well as with major national and international health improvement initiatives.